Ilusi Kemitraan dalam Wacana Ekonomi Berbagi - Hasan Labiqul Aqil (Jurnal DinamikA, 2023)
The emergence of various digital platforms in the era of the internet technology revolution, in addition to giving birth to various new job types, also gives rise to a new term for workers, the term ‘mitra’ in the "gig economy" and gradually replacing previous terms such as buruh, karyawan, pegawai. This article attempts to decode the meaning of "mitra" using Norman Fairclough's critical discourse analysis (CDA) which studies the use of language (verbal and written) as a form of social practice. Through Fairclough's three CDA levels; Text (micro level) is seen as a representation of something containing a certain ideology; Discursive practice (meso level) refers to the production, distribution, and consumption of text; Socio-cultural practice (macro level) refers to the context outside of the text such as the context of society, culture, and politics that influence the existence of text, we can reflect the ideological effects that reproduce unequal power relations in the word "mitra" used by various digital platforms. The term "mitra" referring to the ideology of "platform capitalism" makes them not considered as "pekerja" or "buruh" and eliminating them as legal subjects protected by the Labor Law. The problem is also the new work relationship is still unclear in many aspects, which can lead to exploitation of "mitra" by the company.Keywords: critical discourse analysis, ilusi kemitraan, gig economy, platform capitalism.